Cytokinin-Active Ribonucleosides in Phaseolus RNA: I. IDENTIFICATION IN tRNA FROM ETIOLATED PHASEOLUS VULGARIS L. SEEDLINGS - Edwards, Cynthia A. (1981)
The cytokinin-active ribonucleosides present in tRNA from etiolated Phaseolus vulgaris L. seedlings have been isolated and identified as cis-ribosylzeatin, 2-methylthio-ribosylzeatin, and N(6)-(Δ(2)-isopentenyl)-adenosine. The structures of the compounds were established on the basis of their chromatographic properties and the mass spectra of their permethylated and perdeuteromethylated derivatives. Cis-ribosylzeatin was the major cytokinin-active constituent of tRNA from this source.